Strategic of Defense Management to Navigating the Complexities of CPEC - Lativa Audina Putri; Hikmat Zakky Almubaroq; Ari Pitoyo Sumarno; Untung Hartono (CV. AFDIFAL MAJU BERKAH, 2025)
The China-Pakistan Economic Corridor (CPEC) is a transformative initiative with significant impacts on the economic, social, and environmental landscapes of both countries. This study conducts a comprehensive PESTEL analysis to examine the political, economic, social, technological, environmental, and legal effects of CPEC. The main objective is to understand CPEC's potential to drive economic growth, create employment, solve energy crises, and foster technological advancements, while also addressing challenges such as debt sustainability, social inequality, environmental risks, and legal issues. This qualitative research draws from an extensive review of scholarly articles, reports, and literature to provide valuable insights for policymakers, stakeholders, and researchers involved in large-scale economic projects. The findings emphasize the need for effective governance, equitable benefit distribution, and sustainable development practices to ensure the successful implementation of CPEC.